Evaluation and Comparison between Crude Oil Straight Run Fractions and Its Commercial Fractions (Gasoline, Kerosene and Gas Oil) at Dura Oil Refinery - Al-Dahhan, Wedad H (Al-Nahrain Journal of Science, 2018)
Atmospheric distillation according to ASTM-D 2892 and ASTM-D 86 distillation methods was carried out to one selected crude oil at Dura oil refinery. Its straight run fractions (Gasoline, Kerosene and Gas Oil) were tested using the physical properties: Boiling point, Density, Pour point, Surface tension and Aniline point in addition to the calculated results: API gravity, Kw factor and Correlation index to make a comparison with commercial fractions (refinery final products): Gasoline, Kerosene and Gas Oil. A special distillation curves were obtained for crude oil to determine the straight run fractions and for the commercial fractions to establish their characteristics and support the preliminary results of the physical properties with valuable data which enhanced the comparison. Distillation of commercial gasoline shows that it is heavier than straight run ones, while there were matching in the characteristics for kerosene. Commercial gas oil was lighter than straight run due to the presence of kerosene.